Insights into the nature of self-extinguishing external donors for ziegler-natta catalysis: a combined experimental and DFT study - Vipin Raj, K.; Kumawat, Jugal; Dhamaniya, Sunil; Subaramanian, Murugan; Balaraman, Ekambaram; Kumar Gupta, Virendra; Vanka, Kumar; Grubbs, Robert H. (ChemCatChem, 2021)
Developing donors for Ziegler-Natta (ZN) catalysis to control the polymerization reaction and produce polymers with desirable properties has always been challenging due to the multi-component nature of the catalytic systems. Here, we have developed a new synthetic protocol for making two external donors, D-1 (2,2,2-trifluoroethyl myristate) and D-2 (2,2,2-trifluoroethyl palmitate) that show self-extinguishing properties, followed by a systematic DFT study to understand this peculiar property of these donors. D-1 and D-2 can undergo parallel reactions with aluminum and titanium species present in the system to produce ketones and aldehydes, which are poisons for ZN catalytic systems, thus explaining their self-extinguishing nature. The non-covalent interaction between the long alkyl chain of the donors with the surface plays a vital role in determining the donors ` self-extinguishing nature. There is a significant thermodynamic preference for the binding of the donor with the longer alkyl chain at the titanium center. The current work, therefore, provides interesting insights into how self-extinguishing donors function in ZN catalytic systems.
Keywords: DFT; donors; non-covalent interactions; self-extinguishing; Ziegler-Natta catalysis